Change of Consciusness Level Through Oxygen Supply in Head Injury - Khoiriyah, Khoiriyah; Ardiananto, Hendi (University of Muhammadiyah Semarang, 2019)
Head injury is one of the main causes of death and disability in the productive age group and most occur due to traffic accidents. Patients with a head injury can experience permanent damage to brain tissue or secondary injuries such as brain ischemia due to hypoxia, hypercapnia, hyperglycemia or electrolyte imbalance, even respiratory failure and heart failure. The head injury patients are initially examined using a standardized scoring system to assess the consciousness level of patients with impaired consciousness, namely the Glasgow coma scale (GCS). One of the possible treatments for decreasing intracranial pressure (ICP) and cerebral perfusion managements to position the patients with a head elevation of 15˚-30˚. This treatment aimed to increase venous drainage from the head and to reduce systemic blood pressure that may be compromised by cerebral perfusion pressure. This study aimed to determine the effect of giving oxygen through a simple mask and the 30˚ head elevation position to the changes of the consciousness level for the patients witha head injury in the emergency department at Dr. Kariadi Hospital, Semarang. This study was quasi-experimental research without control with pre-test and post-test one-group design with used a sample of 23 respondents. The instrument used an observation sheet containing the GCS examination results and analyzed using the Wilcoxon test. Based on the results of the bivariate analysis using the Wilcoxon correlation test, a p-value of 0,000 <0,05 was obtained so it could be concluded that the H0 is accepted. Therefore, giving oxygen through simple masks and patient positioning with 30˚ head elevation affect the consciousness level of head injury patients at Dr. Kariadi Hospital, Semarang.